Fatigue behavior and stress distribution of molars restored with MOD inlays with and without deep margin elevation - Grassi, Elisa Donaria Aboucauch [UNESP]; de Andrade, Guilherme Schmitt [UNESP]; Tribst, João Paulo Mendes; Machry, Renan Vaz; Valandro, Luiz Felipe; Ramos, Nathalia de Carvalho; Bresciani, Eduardo [UNESP]; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP] (Springer Nature, 2022)
Objectives: This study evaluated the effect of deep margin elevation (DME) and restorative materials (leucite-reinforced glass–ceramics [C] vs. indirect resin composite [R]) on the fatigue behavior and stress distribution of maxillary molars with 2-mm deep proximal margins restored with MOD inlay. Methods: Fifty-two extracted human third molars were randomly assigned into four groups (n = 13): C; DME + C; R; and DME + R. Inlays were fabricated in CAD-CAM and bonded to all teeth. The fatigue behavior was assessed with the stepwise stress test (10,000 cycles/step; step = 50 N; 20 Hz; initial load = 200 N). Fatigue failure loads and the number of cycles were analyzed with 2-way ANOVA and Tukey’s test (p < 0.05) and Kaplan–Meier survival plots. The stress distribution was assessed with finite element analysis. The models were considered isotropic, linear, and homogeneous, and presented bonded contacts. A tripod axial load (400 N) was applied to the occlusal surface. The stress distribution was analyzed with the maximum principal stress criterion. Results: For fatigue, there was no difference for DME factor (p > 0.05). For the material factor, the load and number of cycles for failure were statistically higher in the R groups (p < 0.05). The finite element analysis showed that resin composite inlays concentrated more stress in the tooth structure, while ceramic inlays concentrated more stress in the restoration. Non-reparable failures were more frequent in the resin composite inlays groups. Conclusions: DME was not negative for fatigue and biomechanical behaviors. Resin composite inlays were more resistant to the fatigue test, although the failure mode was more aggressive. Clinical significance: DME does not impair mechanical behavior. Resin composite inlays failed at higher loads but with a more aggressive failure mode.
Keywords: Composite resins; Dental porcelain; Dental restoration failure; Fatigue fractures; Finite element analysis; Inlays